Lymphocytopenia associated with leucocyte-reduced platelet apheresis: form concern, wane to concern again - GUO Yongjian; WANG Limei; ZENG Jia (Zhongguo shuxue zazhi)
In the early stage of the application of platelet apheresis technology, there was a concern that high-frequency platelet apheresis might lead to the risk of lymphocyte depletion in blood donors. With the advances in platelet apheresis technology and improvements in collection purity and efficiency, this concern was waning. In recent years, with the wide application of leucocyte-reduced platelets apheresis, this issue has once again become a concern and research hotspot in the international blood transfusion research field. We briefly review this concern and focus on the research progress in recent years and put forward some suggestions to reduce this potential risk and of further research.